Problems with the Competition Policy Formation in Georgia - Orjonikidze, Nino; Nino Liparteliani, (European Journal of Multidisciplinary Studies, 2018)
In Georgia, since the declaration of independence, there has always existed an attempt to establish legal and regulatory mechanisms that would improve competition. Numerous laws and legal acts were formed with the purpose to analyze the process of holding dominant positions by economic agents at markets, to eliminate the abuse of such positions, to reveal the attempts of limited competition at market, as well as to provide established market with fair competition rules. Georgia has always aspired to integrate with European Union structures. The country is a member of World Trade Organization and a part of multiple bilateral, regional, multilateral agreements and international organizations (that collaborate within international competition field) as a full member or as an observer. Based on the above mentioned issues, the improvement of competition policy becomes inevitable in Georgia.
Keywords: competition, antimonopoly regulation, euro-integration, regulation, monitoring.